The factors of corporate hedging using financial derivatives: Why French non-financial companies hedge? - Tosun, Melek (2019)
This dissertation is empirically studying the determinants of hedging with financial derivatives by French non-financial firms. Data of 192 firms have been selected and analysed over a period of 6 years, between 2011 and 2016. Data about firms’ hedging instruments have been extracted from annual reports, which have been downloaded from companies’ website, with a key word approach. Moreover, some databases like Bloomberg, Datastream have been used. Univariate, multivariate and linear regression have been run on the original sample, then on the both FX and IR exposed, on the only FX exposed and on the only IR exposed subsamples. Tests permit to get an idea about the motives for corporate hedging for French non-financial firms. The eventual biases have also been treated. Outcomes are showing that some factor are significantly impacting hedging decision of companies. An alternative definition of hedger has also been tested. Proxies have been selected for each factor. Outcomes confirm that proxies were well chosen. Companies’ size and their FX exposure are mainly explaining the hedging behaviour. Finally, liquidity can be used to substitute hedging.